Breed Ancestry, Divergence, Admixture, and Selection Patterns of the Simbra Crossbreed - van der Nest, Magriet A.; Hlongwane, Nompilo; Hadebe, Khanyisile; Chan, Wai-Yin; van der Merwe, Nicolaas A.; De Vos, Lieschen; Greyling, Ben; Kooverjee, Bhaveni B.; Soma, Pranisha; Dzomba, Edgar F.; Bradfield, Michael; Muchadeyi, Farai C. (Frontiers in Genetics, 2021)
In this study, we evaluated an admixed South African Simbra crossbred population, as well as the Indicine and Simmental ancestor populations to understand their genetic architecture and detect genomic regions showing preferential signatures selection. Animals were genotyped using the Illumina BovineLD v2 BeadChip (7K). Genomic structure analysis revealed that the South African Simbra breeds have an admixed genome, composed of 5/8 Taurine and 3/8 Indicine, ensuring that the Simbra genome maintains favourable traits from both breeds. Genomic regions that have been targeted by selection were detected using the linkage disequilibrium-based methods iHS and Rsb. These analyses identified 10 candidate regions potentially under strong positive selection, containing genes previously implicated in cattle health and production (e.g. TRIM63, KCNA10, NCAM1, SMIM5, MIER3 and SLC24A4). These adaptive alleles likely contribute to the biological and cellular functions determining phenotype in the Simbra hybrid cattle breed. Our data suggested that these alleles were introgressed from the breed’s original indicine and taurine ancestors. The Simbra breed has thus derived parental alleles that combine the superior traits of the founder Brahman (Indicine) and Simmental (Taurine) breeds. These regions and genes might represent good targets for ad-hoc physiological studies, selection of breeding material and eventually even gene editing, for improved traits in modern cattle breeds. Ultimately, this study represents an important step towards developing and improving strategies for selection and breeding populations to ultimately contribute meaningfully to the beef production industry.